The matrix [videorecording (DVD)] - Reeves, Keanu; Fishburne, Laurence, III, 1961-; Wachowski, Lilly, 1967-; Wachowski, Lana, 1965-; Moss, Carrie-Anne, 1970- (Warner Home Video, 2001)
In an anti-utopian future, the "real" world as we know it is nothing more than a computer construct, created by an all-powerful artificial intelligence. A small group of humans has found a way out of the construct, and are now fighting for the future of the human race.